Catalyst-mediated doping in electrochemical growth of solar silicon. (20th January 2021) - Cho, Sung Ki; Lim, Taeho
Highlights: Electrochemical growth of Si from SiO2 in CaCl2 melt is capable of in situ doping. Controllable doping into Si is mediated by Ag liquid catalyst on Si. Doping density can be estimated from I–E measurement and Mott–Schottky plot analysis. The mechanism for catalyst-mediated Si doping is proposed. Abstract: The direct electrochemical reduction of silicon dioxide in molten CaCl2 has been investigated as a promising candidate for alternative production process of solar silicon. Herein, we study a catalyst-mediated doping, which is carried out by introducing dopant precursors like Al2 O3, In2 O3, and Sb2 O3 into the molten CaCl2 during the electrochemical growth of silicon on Ag catalyst. The photoelectrochemical measurement demonstrates controllable p -type or n -type doping, and the photoresponse of doped silicon reaches 1.1±0.4 mA/cm 2 under 100 mW/cm 2 irradiation. Doping densities, estimated from two-point micro-probe measurements and Mott–Schottky plot analyses range from 10 15 to 10 16 /cm 3 . Dopant is incorporated through Si–Ag catalyst droplet, which is supported by a high dopant content in Ag catalyst revealed by the elemental mapping of secondary ion mass spectroscopy. The catalyst-mediated doping mechanism is proposed to elucidate the doping level. The liquid droplet is presumed to be under local equilibrium along with significant loss of the dopant from it whereby the doping level becomes a function of the segregation coefficient and the rate constant of the electrochemical reaction. Graphical abstract: Image, graphical abstract